How task difficulty and academic self-efficacy impact retrieval practice guidance - Liao, Chenchen; Zhang, Jinkun (Frontiers in Psychology, 2023)
Retrieval practice can enhance learning but is rarely used in self-regulated learning. Although explicit retrieval practice guidance (RPG)—which helps students use retrieval correctly—can improve learning outcomes, however, task difficulty and differences in academic self-efficacy (ASE) may influence retrieval practice decisions and learning performance, which were not considered in previous researches. The purpose of this study was to explore whether RPG produces different effects due to task difficulty and ASE. In Experiment 1, participants studied tasks with varying difficulty levels, some of which were guided. Results showed that RPG could enhance learning through increased retrieval practice, and participants engaged in more retrieval for difficult tasks. In Experiment 2, participants with different degrees of ASE learned tasks under guidance. Participants with high ASE persisted better on different tasks. Hence, task difficulty can affect retrieval practice decisions, and ASE increases persistence in retrieval practice. The implications of the findings for students’ use of RPG are discussed in this article.